Legal Certainty in the Enforcement of Copyright Infringement on E-Commerce Platforms in Indonesia - Leonardo, Steven; Sudirman, Lu; Disemadi, Hari Sutra (Universitas Musamus, 2025)
Although Indonesia has Law No. 28 of 2014 on Copyright, the legal problems of copyright infringement in transactions on e-commerce platforms are legal regulations regarding the enforcement of copyright infringement and the awareness of e-commerce platform users. There is a gap between the current law and the reality on the ground, and piracy is still widespread. The purpose of this study is to analyze legal certainty in the enforcement of copyright infringement on e-commerce platforms based on the current law and to identify challenges in its enforcement. The method used in this research is a normative legal research method that involves analyzing laws and regulations, legal theories, and literature related to copyright and e-commerce issues. The findings of this study recommend the reconstruction of copyright enforcement on e-commerce platforms in Indonesia through the integration of advanced technologies such as Artificial Intelligence (AI) and automated algorithms to effectively detect and monitor violations, accompanied by the simplification of administrative processes. Additionally, it emphasizes the importance of defining specific responsibilities for e-commerce platforms, strengthening sanctions for royalty payment violations, and increasing legal awareness among users through educational campaigns and transaction agreements that include copyright protection to ensure legal certainty in the digital era.